Familial isolated hyperCKaemia associated with a new mutation in the caveolin-3 (CAV-3) gene. Issue 1 (1st July 2002) - Merlini, L; Carbone, I; Capanni, C; Sabatelli, P; Tortorelli, S; Sotgia, F; Lisanti, M P; Bruno, C; Minetti, C
Abstract : An 18 year old man and his mother both presented with persistent, isolated raised serum creatine kinase (hyperCKaemia) without muscle symptoms. Analysis of caveolin-3 protein expression in muscle biopsy of the propositus showed a reduction in the protein. Genetic analysis revealed a new heterozygous mutation in the caveolin-3 (CAV-3) gene: a C→T transition at nucleotide position 83 in exon 1 leading to a substitution of a proline for a leucine at amino acid position 28 (P28L). This is the first pathogenic mutation in the CAV-3 gene associated with isolated familial hyperCKaemia. It expands the genetic heterogeneity in patients with caveolin-3 deficiency and confirms that caveolin-3 deficiency should be considered in the differential diagnosis of isolated hyperCKaemia.